PERSEPSI MASYARAKAT DALAM PENGGUNAAN TEKNOLOGI INFORMASI PADA TRANSPORTASI PUBLIK STUDI KASUS BRT BANDAR LAMPUNG - Syah Riza Nur Adha; Rahayu Sulistyorini; Muhammad Zainal Ibad (Jurnal Perencanaan dan Pengembangan Kebijakan, 2022)
With the development of increasingly large technology, the distribution of information is now more easily accessible from outside and within the country. From the development of this technology, Indonesia is not spared in using it in people's daily lives such as in communicating, traveling, general information and specific information and others. Even though they already have urban public transportation in Bandar Lampung, many people still use private vehicles which causes urban roads to be increasingly congested by private vehicles. To increase public interest in using public transportation, especially BRT, this is the background of this research. The aim is to identify public perceptions in the use of information technology in public transportation, especially the Bandar Lampung Bus Rapid Trans (BRT). The approach method used is a quantitative approach method with descriptive analysis and data obtained from primary and secondary data. The results obtained are in the form of public perceptions of the system to be developed, the need for features that can be included, and the potential with the application, all of which are based on transport behavior variables.